A Review on Prediction over pressured zone in hydrocarbon well using seismic travel time through artificial intelligence technique for pre-drilling planning - Haravinthan , A (2011)
A Review on Prediction over pressured zone in hydrocarbon well using seismic travel time through artificial intelligence technique for pre-drilling planning